Dietary Administration of Banana (Musa acuminata) Peel Flour Affects the Growth, Antioxidant Status, Cytokine Responses, and Disease Susceptibility of Rohu, Labeo rohita - Sib Sankar Giri; Jin Woo Jun; Venkatachalam Sukumaran; Se Chang Park (Journal of Immunology Research)
To explore the feasibility of Musa acuminata (banana) peels as a feed additive, effects of banana peel flour (BPF) on the growth and immune functions of Labeo rohita were evaluated. Diets containing five different concentrations of BPF (0% [basal diet], 1% [B1], 3% [B3], 5% [B5], and 7% [B7]) were fed to the fish (average weight: 15.3 g) for 60 days. The final weight gain and specific growth rate were higher (P<0.05) in the B5 group. The most significant improvements in immune parameters such as lysozyme, alternative complement pathway, leukocyte phagocytic, superoxide dismutase, and catalase activities were observed in the B5 group. However, the B5 group exhibited the lowest malondialdehyde activity. IgM and glutathione peroxidise activities were significantly elevated in the treatment groups, except in B1, after only 30 days of feeding. Of the examined cytokine-related genes, IL-1β, TNF-α, and HSP70 were upregulated in the head kidney and hepatopancreas, and expressions were generally higher in the B3 and B5 groups. Moreover, B5 group challenged with Aeromonas hydrophila 60 days after feeding exhibited the highest survival rate (70%; P<0.05). These results suggest that dietary BPF at 5% could promote growth performance and strengthen immunity in L. rohita.